2012
DOI: 10.1016/j.jsps.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness and scientific accuracy of private sector Arabic language patient drug information leaflets

Abstract: The study results are consistent with those of previous quality content studies of commercially available English patient drug information leaflets. The results have important implications for patients as access to a reliable source of drug information may prevent harm or limit the suffering from serious adverse drug reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Our results are concordant with other studies that have found a large degree of inconsistency in risk communication between healthcare professional and consumer audiences, both within and across countries . While other researchers considered the quantity or presence/absence of information overall and usefulness of information, this study is the first to our knowledge to focus on how professional and consumer labeling conveys risk information when the state of knowledge is incomplete, contradictory or inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are concordant with other studies that have found a large degree of inconsistency in risk communication between healthcare professional and consumer audiences, both within and across countries . While other researchers considered the quantity or presence/absence of information overall and usefulness of information, this study is the first to our knowledge to focus on how professional and consumer labeling conveys risk information when the state of knowledge is incomplete, contradictory or inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“…; Sukkari et al. ). Few articles have compared safety information listed in the PIs across countries and regulatory systems.…”
Section: Introductionmentioning
confidence: 97%
“…Drug information from different resources that is available to healthcare professionals has previously been studied (Dunne et al 1973;Silverman 1976;Alloza and Lasagna 1983;Bawazir et al 1991;Reggi et al 2003;Malinowski et al 2008;Sawalha et al 2008;Sasich et al 2009;Sukkari et al 2012). Few articles have compared safety information listed in the PIs across countries and regulatory systems.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the findings of the current study showed that nearly 50% of cases met the standards; in previous studies, the overall compliance was less. For instance, Sukkari et al 24 investigated Arabic PIs with keystone criteria of the United States and found that only 30% of the PIs produced complied with the standard in question. A study published in Nepal on PIs advertising medicines revealed that the pharmaceutical and advertising PIs did not comply with the standards of the WHO; in most cases, the health profile of the medicine, such as side effects or adverse effects of medicine, precautions and drug interactions, were ignored.…”
Section: Discussionmentioning
confidence: 99%